Corrosion protection properties of different inhibitors containing PEO/LDHs composite coating on magnesium alloy AZ31 - Gen Zhang (Nature Portfolio, 2021)
Abstract Corrosion inhibitors 2,5-pyridinedicarboxilate (PDC), sodium metavanadate (SMV) and 5-aminosalicylate (AS) were impregnated into porous PEO coatings respectively via vacuuming process, followed by fast sealing treatment in a Ce containing solution. After that layered double hydroxides (LDHs) based nanocontainers were respectively prepared on them via hydrothermal treatment. In frame of this work it was shown, that sealing effect for the pore was provided by formation of new phase CeO2 on the surface of PEO coatings. And, hydrothermal preparation for preparing LDHs leaded obvious changes in structure and thickness of the coatings. In addition, impregnation of inhibitors was in favor of improving LDHs content in final composite coatings. EIS result indicated that AS/Ce-HT specimen exhibited a best corrosion protection.